The impact of sea level rise on geodetic vertical datum of Peninsular Malaysia - Din, A. H. M. (International Society for Photogrammetry and Remote Sensing, 2016)
Sea level rise is rapidly turning into major issues among our community and all levels of the government are working to develop responses to ensure these matters are given the uttermost attention in all facets of planning. It is more interesting to understand and investigate the present day sea level variation due its potential impact, particularly on our national geodetic vertical datum. To determine present day sea level variation, it is vital to consider both in-situ tide gauge and remote sensing measurements. This study presents an effort to quantify the sea level rise rate and magnitude over Peninsular Malaysia using tide gauge and multi-mission satellite altimeter. The time periods taken for both techniques are 32 years (from 1984 to 2015) for tidal data and 23 years (from 1993 to 2015) for altimetry data. Subsequently, the impact of sea level rise on Peninsular Malaysia Geodetic Vertical Datum (PMGVD) is evaluated in this study. the difference between MSL computed from 10 years (1984 ' 1993) and 32 years (1984 ' 2015) tidal data at Port Kelang showed that the increment of sea level is about 27mm. The computed magnitude showed an estimate of the long-term effect a change in MSL has on the geodetic vertical datum of Port Kelang tide gauge station. This will help give a new insight on the establishment of national geodetic vertical datum based on mean sea level data. Besides, this information can be used for a wide variety of climatic applications to study environmental issues related to flood and global warming in Malaysia.